2020
DOI: 10.1038/s41416-020-0952-1
|View full text |Cite
|
Sign up to set email alerts
|

YES1 amplification confers trastuzumab–emtansine (T-DM1) resistance in HER2-positive cancer

Abstract: Background Trastuzumab–emtansine (T-DM1), one of the most potent HER2-targeted drugs, shows impressive efficacy in patients with HER2-positive breast cancers. However, resistance inevitably occurs and becomes a critical clinical problem. Methods We modelled the development of acquired resistance by exposing HER2-positive cells to escalating concentrations of T-DM1. Signalling pathways activation was detected by western blotting, gene expression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 51 publications
0
20
0
5
Order By: Relevance
“…4G). Taken together, we demonstrate that by destabilizing ERBB2, that we controlled and downregulated YES1 and WNK1 that are well known causes of drug resistance in ERBB2+ trastuzumab drug resistant and in osimertinib resistant EGFR T790M lung cancer (28)(29)(30)(31).…”
Section: S2a-b List S2)mentioning
confidence: 59%
“…4G). Taken together, we demonstrate that by destabilizing ERBB2, that we controlled and downregulated YES1 and WNK1 that are well known causes of drug resistance in ERBB2+ trastuzumab drug resistant and in osimertinib resistant EGFR T790M lung cancer (28)(29)(30)(31).…”
Section: S2a-b List S2)mentioning
confidence: 59%
“…The possibility that YES1 might serve as a therapeutic target for breast cancer therapy as a means of overcoming drug resistance has already been reported. Previous studies showed the role of YES1 amplification in T-DM1 [ 22 ], trastuzumab and lapatinib [ 7 ], and neratinib [ 19 ] regimens. Among members of the Src family, YES1 expression showed the highest association with poor outcomes in patients with non-small cell lung cancer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…33 They suggested using Yes and HER2 inhibitors together in attempts to better counteract resistance developed to ado-trastuzumab emtansine. 33 Another agent that was found to be able to overcome the resistance is SYD985, a second-generation antibody drug conjugate. 34 D’Amico et al.…”
Section: Clinical Use Controversiesmentioning
confidence: 99%
“…32 Wang et al found that the cells that were resistant to ado-trastuzumab emtansine had overexpressed Yes, which in turn activated EGFR, PI3K, and MAPK pathways. 33 They suggested using Yes and HER2 inhibitors together in attempts to better counteract resistance developed to ado-trastuzumab emtansine. 33 Another agent that was found to be able to overcome the resistance is SYD985, a secondgeneration antibody drug conjugate.…”
Section: Clinical Use Controversiesmentioning
confidence: 99%
See 1 more Smart Citation